2013
DOI: 10.1021/jp309102c
|View full text |Cite
|
Sign up to set email alerts
|

Solvate Structures and Computational/Spectroscopic Characterization of Lithium Difluoro(oxalato)borate (LiDFOB) Electrolytes

Abstract: Lithium difluoro(oxalato)borate (LiDFOB) is a relatively new salt designed for battery electrolyte usage. Limited information is currently available, however, regarding the ionic interactions of this salt (i.e., solvate formation) when it is dissolved in aprotic solvents. Vibrational spectroscopy is a particularly useful tool for identifying these interactions, but only if the vibrational bands can be correctly linked to specific forms of anion coordination. Single crystal structures of LiDFOB solvates have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 68 publications
5
69
0
Order By: Relevance
“…A roughened gold electrode was used as the working electrode, coupled with a lithium plate as the counter/reference electrode. [20] This confirmed the formation of PEC layer when the cell in E2 was discharged to 1.5 V. The results were further explored by Fourier-transform infrared spectroscopy (FT-IR). Both in E1 and E2, the electrodes at 3 V show the same vibrational spectra, which are corresponding to solvent species (Figure 2a,b).…”
Section: Doi: 101002/aenm201803715supporting
confidence: 53%
“…A roughened gold electrode was used as the working electrode, coupled with a lithium plate as the counter/reference electrode. [20] This confirmed the formation of PEC layer when the cell in E2 was discharged to 1.5 V. The results were further explored by Fourier-transform infrared spectroscopy (FT-IR). Both in E1 and E2, the electrodes at 3 V show the same vibrational spectra, which are corresponding to solvent species (Figure 2a,b).…”
Section: Doi: 101002/aenm201803715supporting
confidence: 53%
“…By comparing the peak assignments of LiDFOB with LiBOB, many of the vibrational bands were shared due to a common oxalate group. The DFOB¯anion displayed out-ofphase valence vibration at 1761 cm −1 , as well as an in-phase valence vibration at 1794 cm −1 , corresponding to C═O vibrations [28]. It is also observed that the peak intensity gradually increased with the increase of LiDFOB salt in polymer-salt complex.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 82%
“…A more descriptive classification than for simpler anionssuch as BF 4 − and ClO 4 − which are not flexible and thus have only a single conformation resulting in fewer modes of Li + cation coordination 1−3 is therefore necessary for Li + cation coordination by the TFSI − anion (Chart 1): SSIP uncoordinated anion CIP-I 1 anion O coordinated to 1 Li + CIP-II 2 anion O coordinated to 1 Li + AGG-Ia 2 anion O coordinated to 2 Li + AGG-Ib 3 anion O coordinated to 2 Li + AGG-IIa 3 anion O coordinated to 3 Li + AGG-IIb 4 anion O coordinated to 3 Li + AGG-III 4 anion O coordinated to 4+ Li + As part of the present evaluation, different crystalline solvates were prepared and analyzed based upon this classification. The results reported here make it clear that a rigorous deconvolution of specific forms of TFSI − ···Li + cation coordination for electrolyte liquid mixtures is a difficult challenge.…”
Section: Introductionmentioning
confidence: 99%